Byzantine tragedy in Restoration England: Joseph Simons's Zeno and Sir William Killigrew's The Imperial Tragedy. Issue 4 (September 2016) - Shell, Alison
Abstract: The history of the Byzantine era is rich in dramatic potential, and was extensively exploited by writers of continental Catholic school and college drama in the early modern period. However, it was hardly ever drawn upon within Tudor and Stuart professional drama. One exception to this rule is Zeno, written by Joseph Simons SJ, freely adapted by Sir William Killigrew and printed in 1669 under the title The Imperial Tragedy . Killigrew's play is also unusual because plays written and performed in the English Catholic colleges on the continent during the sixteenth and seventeenth centuries were very seldom acknowledged, printed or adapted on the English mainland. The adaptation suggests a personal relationship between the two playwrights. Simons was attached to the London court at this period as Jesuit Provincial; Killigrew, a courtier, appears to have been on friendly terms with Simons in the late 1660s, and to have wanted to pay him a compliment by adapting his play. However, he printed it anonymously, not mentioning either Simons's name or his own. It is likely that he did this because Simons was a controversial associate: not least for his influence over the future James II, whom he converted to Roman Catholicism. Killigrew appended a tantalising title page to his work, suggesting that there was more to his anonymity than mere modesty, and came clean about his authorship to the semi‐private audience with which he also shared his revisions: an audience which included at least one individual with a pronounced interest in religious toleration. At this time, the gift of books could cement literary and personal alliances, and manuscript circulation could define friendship and patronage networks. The two surviving copies of The Imperial Tragedy annotated by Killigrew give us something in between: a case study of how an author's previously printed material could be personalized by religiously sensitive manuscript additions for an inner circle.